Fairness in Korean Society: Assessing the Perspective of Millennials - Kim, Jeffrey (Technium Social Sciences Journal, 2020)
This study aims to evaluate the recent "Fairness" related issues in South Korea in the perspectives of the Millennials. In contrast to the X generation, the Millennials are living through the hardest period of Korea with the difficulty of accumulating wealth, high unemployment, and tough social mobility. The challenges in the country led more millennials to lean on a fairer society and to support the current administration, the Moon Administration. However, "Fairness" issues are arising continuously and the response to those issues vary, depending on the typical factors. By analyzing three recent issues-Cho Kuk Incident, ICN Incident, and the Yonsei Incident- the paper analyzes the selective rage of the Millennials. The level of rage is tied to the social, political status of the figure and the direct connection to employment. The policymakers and the X generations emphasize the importance of a fair society while they are not willing to give up their shares of the pie. To avoid slowing down in social and economic development, Korea should find a practical solution or else the Millennials will be living through the toughest generation of Korea.